Study on the Prevalence of Low Back Pain based on Age and Gender in Indonesian Hajj Pilgrims: Period 1438 – 1443 H - Zaki, Achmad; Rufaidah, Melia Fatrani; Mahendra, Maulana Ihza; Mardjikoen, Bisatyo; Maikel, Mahesa Paranadipa (The Avicenna Medical Journal, 2024)
Background: Musculoskeletal pain is a common complaint in men and women with a wide age range and in all sociocultural groups. Low back pain significantly contributes to the overall burden of musculoskeletal conditions. In 2020, low back pain (LBP) affected 619 million people globally and it is estimated that the number of cases will increase to 843 million cases by 2050, driven largely by population expansion and ageing.1 Hajj is a series of worship with high demands on physical strength, and musculoskeletal pain experienced by the pilgrims will significantly affect the worship and the pilgrims' classification of health, known as health istithaah. Objective: This study aims to determine the prevalence of low back pain incidence based on the age and gender of Indonesian pilgrims in periods 1438-1443 H. Methods: This descriptive study with a cross-sectional design used secondary data from Health Information System for Indonesian Hajj Pilgrims (SISKOHATKES) with a period of Hajj from 1438 H until 1443 H. Results: This study showed that the prevalence of Indonesian pilgrims in 1438-1443 H diagnosed with low back pain in Saudi Arabia based on age group was highest at 46 years and over each year. However, the prevalence of female sex was not consistently higher than male in 1438-1443 H. The percentage of the male sex (0.020%) was higher than the female sex (0.016%) in 1438 H, and the female sex was consistently higher than the male sex in 1439 – 1440 H, while in 1443 H, the male and female sexes had the same proportion. Conclusion: Indonesian pilgrims aged 46 years and over with a diagnosis of low back pain have a higher prevalence in each year of examination, and female and male pilgrims do not consistently have a higher prevalence value in the period 1439 - 1443 H